Benefits of Using High-Volume–Low-Pressure Tracheal Tube in Children Undergoing Congenital Cardiac Surgery: Evidence From a Prospective Randomized Study. (September 2018) - Chand, Rakesh; Roy Chowdhury, Saibal; Rupert, Emmanuel; Mandal, Chandan Kumar; Narayan, Pradeep
Background. In the past 2 decades, usage of high-volume–low-pressure microcuffed tracheal tubes in smaller children has increased. However, there is paucity of evidence of its usage in smaller children undergoing congenital cardiac surgery. The aim of this study was to assess if microcuff endotracheal tubes in neonates and younger children undergoing congenital cardiac surgery is associated with better outcomes than uncuffed tubes. Methods . We carried out this single-center, prospective, randomized study between June and November 2016. Eighty patients were randomized into those receiving microcuff tracheal tubes and conventional uncuffed tubes. Primary outcome was stridor postextubation. Secondary outcomes measured included number of tube changes, volume of anesthetic gases required, and cost incurred. Results. The 2 groups were comparable in terms of baseline characteristics and duration of intubation. Incidence of stridor was significantly higher in conventional uncuffed tubes (12 [30%] vs 4 [10%]; P = .04) and so was the number of tube changes required (17/40 [42.5%] vs 2/40 [5%]; P ≤ .001). Tube change was associated with more than 3-fold risk of stridor (odds ratio = 3.92; 95% confidence interval = 1.23-12.43). Isoflurane (29.14 ± 7.01 mL vs19.2 ± 4.81 mL; P < .0001) and oxygen flow requirement ( P < .0001) and the resultant cost (7.46 ± 1.4 vs 5.77 ± 1.2 US; P < .0001) were all significantly higher in the conventional uncuffed group. Conclusion. Microcuff pediatric tracheal tube is associated with significantly lower incidence of stridor, tube changes, and anesthetic gas requirement. This leads to significant cost reduction that offsets the higher costs associated with usage of a microcuff tracheal tube.